PSYCHOLOGICAL PROBLEMS AFFECTING YOUTH'S PROFESSIONAL CHOICE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses in detail the social problems that arise among young people in today's developing era in choosing the right profession and choosing a profession, as well as the psychological processes and problems that affect them.